2011
DOI: 10.1002/adma.201103361
|View full text |Cite
|
Sign up to set email alerts
|

PS‐b‐P3HT Copolymers as P3HT/PCBM Interfacial Compatibilizers for High Efficiency Photovoltaics

Abstract: A conducting diblock copolymer of PS-b-P3HT was added to serve as a compatibilizer in a P3HT/PCBM blend, which improved the power-conversion efficiency from 3.3% to 4.1% due to the enhanced crystallinity, morphology, interface interaction, and depth profile of PCBM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
101
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 112 publications
(105 citation statements)
references
References 33 publications
(16 reference statements)
4
101
0
Order By: Relevance
“…Midblock conformational fractions and copolymer morphologies are provided as functions of copolymer composition and temperature. Block copolymers remain one of the most extensively studied genres of macromolecules to date due to their intrinsic ability to (i) self-organize spontaneously into a wide variety of periodic nanostructures 1, 2 and (ii) compatibilize immiscible polymers, 3,4 as well as stabilize polymer nanolaminates, 5,6 by locating at polymer/polymer interfaces. These intriguing soft materials can likewise form molecular and supramolecular networks upon microphase separation.…”
mentioning
confidence: 99%
“…Midblock conformational fractions and copolymer morphologies are provided as functions of copolymer composition and temperature. Block copolymers remain one of the most extensively studied genres of macromolecules to date due to their intrinsic ability to (i) self-organize spontaneously into a wide variety of periodic nanostructures 1, 2 and (ii) compatibilize immiscible polymers, 3,4 as well as stabilize polymer nanolaminates, 5,6 by locating at polymer/polymer interfaces. These intriguing soft materials can likewise form molecular and supramolecular networks upon microphase separation.…”
mentioning
confidence: 99%
“…This is due to an increasing interest in taking advantage of the nanometer scale resolution provided by neutron reflectometry (NR)/scattering to probe the structure, interface and morphology of bulk heterojunctions (BHJ) in organic photovoltaics (OPV) [9][10][11][12][13][14][15] to determine not only the nanoscopic heterogeneity of donor/acceptor components, but their degree of mixing and the vertical composition. The nanoscopic morphological information provided by isotopic substitution is highly relevant to understand exciton diffusion and charge transport in these devices [9][10][11][12][13][14][15] ; however, deuteration is commonly believed to have little effect on morphology. Only recently, small-angle neutron scattering revealed that deuterium substitution can significantly influence the phase separation kinetics and morphology in some polymer blend systems 16,17 .…”
mentioning
confidence: 99%
“…Subsequently, Sun et al utilized 5 wt% copolymer additive polystyrene-block-poly(3-hexylthiophene) (PS-b-P3HT) to obtain favorable BHJ morphology with increased PCEs from 3.3% to 4.1% [49]. The authors elucidated that the additive-induced morphology was resulted from the interaction of PS segment with PC61BM phase and P3HT block with P3HT phase as shown in Figure 3b.…”
Section: Copolymermentioning
confidence: 99%